Idealistic Vision or Reality? Life-long Learning Among the Romany Ethnic Groups - G. Fekete, Éva; T. Hargitai, Judit; Jász, Krisztina; Szarvák, Tibor; Szoboszlai, Zsolt (Discussion Papers, 2012)
The era that we live in can be regarded as the era of the knowledge society. It is everyone’s right and obligation to find their place in the area of knowledge and in the modern and traditional relation systems. Are the chances of getting into this situation given to all social groups? Can the shrinking Hungarian society afford to give up helping the Romany population to catch up, especially as they are a demographically very active group of society? In our opinion the answer is no, and as a part of the Romany popula¬tion expresses their needs to join the modernisation process, it is certainly well worth looking for the tools that will support their efforts to catch up. In establish¬ing the conditions of general development life-long learning may become a useful measure, which can become a tool in assisting the changes of individuals’ habits and closing the gap between Romany groups and the rest of society. Are the conditions of “prescience” and “prediction” given in the Romany soci¬ety? In the research geared to analyse the preconditions of life-long learning we attempted to reveal the social and individual factors that will help the Romany society to dedicate their existence to ‘prescience’ and ‘prediction’ more effi¬ciently.